1/u+6=-6

Simple and best practice solution for 1/u+6=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/u+6=-6 equation:


D( u )

u = 0

u = 0

u = 0

u in (-oo:0) U (0:+oo)

1/u+6 = -6 // + 6

1/u+6+6 = 0

1*u^-1 = -12 // : 1

u^-1 = -12

-1 < 0

1/(u^1) = -12 // * u^1

1 = -12*u^1 // : -12

-1/12 = u^1

u = -1/12

u = -1/12

See similar equations:

| -3(2s-3)-9=-2(7s+7)-2 | | x*y=1512 | | 10x-4x= | | 6timesx=4 | | 5(x-7)=40 | | 5z-10z=45 | | y=-3/5x+b | | -1xy+2x^2+-6y^2= | | 6x^2-3xy-18y^2= | | (2/x-7)=3 | | (11b-4)-5(2b+1)=-5 | | 2x^7+2x^6-4x^5= | | (9x-9/7)+(8-x/3)=9 | | 9x+5x+3+8=11x+4+2x | | 33*w=52 | | (6x^2+22+17)/(x+3) | | w*2w-5=52 | | 2w^2-5w-17-w^2+2w-1=0 | | 2w^2-5w-17-w^2+2w-1=00 | | 2u^2-24u+70-u^2+14u-49=0 | | 2w^2-3w-16-w^2+4w-4=0 | | 2x^2-8x-8-x^2+4x-4=0 | | (x+2)/(x-6)=55 | | 2v^2+v+30-v^2+8v-16=0 | | 2y^2-3y+5-y^2+6y-9=0 | | 2m-4+12=3m-4+2 | | 2y^2-3y+5-y^2-6y+9=0 | | 2y^2-3y+5+y^2-6y+9=0 | | 24x^2-49x-40=0 | | 2m-4+12=2m-4+12 | | -12x^2+45x+12=0 | | 2y^2-y-29-y^2+2y-1=0 |

Equations solver categories